SISTEM INFORMASI PERSEDIAAN BAHAN ROTI PADA PAPIBUN BAKERY MENGGUNAKAN METODE FIFO (FIRST IN FIRST OUT) DAN LIFO (LAST IN FIRST OUT) - SUPRIYADI, ARIF (Jejaring Penelitian dan Pengabdian Masyarakat (JPPM), 2024)
CV Papibun Bakery is a CV that operates in the field of selling food which is produced every day and lots of production materials go in and out for the food production process. Previously, CV Papibun Bakery still used manual methods such as records in ingredient inventory, where ingredient stock records were sometimes lost or damaged, and ingredients coming in and out were still irregular, which could cause the ingredients to expire because they were stored for too long. For this reason, CV Papibun Bakery needs a system that can manage the inventory of digital production materials and regulate the entry and exit of materials using methods such as FIFO (First In First Out) and LIFO (Last In First Out), making it easier for employees to manage material inventories, and materials that go in first must go out first to reduce the risk of materials that could expire. This can also guarantee that production is always of high quality and customers get the best quality from CV Papibun Bakery